Strategies for promoting professionalism in secretarial practice for effective job performance and improved productivity - Buhari, Ganiyu Idowu (Journal of Professional Secretaries and Office Administrators, 2014)
More than ever before, secretarial practitioners face challenging role as modern office managers. This, and in the spirit of concept of international best practices, make it imperative for secretarial practitioners to perform secretarial functions in a professional manner. It is on the basis of the above background that the writer intends to assess the strategies for promoting professionalism in secretarial practice for effective job performance and improved productivity. The paper therefore attempts to examine the meaning of professionalism and its benefits, meaning of a professional secretary and his attributes. It also looks at anti-professional activities and strategies to curb professional misconduct. It concludes, making appropriate recommendations, amongst others, collaborative efforts to fight unprofessional behaviours.